User-Centered Design Evaluation of ShopeeFood Driver User Interface and Experience - Azhari Yudistya Nurrahman; Aries Dwi Indriyanti (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2026)
The ShopeeFood Driver application serves as a critical tool for delivery partners in managing orders and navigation. However, initial observations and user interviews conducted in Surabaya identified several usability issues, including the absence of demand visualization (heatmaps), lack of destination-based order filtering, and the inability for drivers to rate customers. This study aims to evaluate and redesign the UI/UX of the ShopeeFood Driver application using the User-Centered Design (UCD) method to enhance operational efficiency and user satisfaction. The research followed the four stages of the UCD process: understanding the context of use, specifying user requirements, producing design solutions, and evaluating against requirements. Data were collected from 30 active delivery partners in Surabaya through observations, semi-structured interviews, and System Usability Scale (SUS) questionnaires. The redesign introduced three key features: an order-demand heatmap, a destination-based (one-way) order filter, and a customer rating system. Post-redesign evaluation demonstrated significant improvements in usability. Effectiveness increased from 82.8% to 100%, while efficiency improved as the average task completion time decreased from 34.7 seconds to 21.7 seconds. Additionally, the average SUS score increased from 66.75 (Marginal/OK) to 87.25 (Acceptable/Excellent). These results indicate that the application of the UCD method successfully addressed operational challenges at the field level and substantially improved the usability of the ShopeeFood Driver application, resulting in a more intuitive and efficient user experience for delivery partners.